A formação da identidade do estudante do ensino superior de tecnologia em gastronomia e o projeto político pedagógico - CASTRO, Fabiano Souza de Almeida (2019)
This study, affiliated to the research line of Formation and Action of the Teaching Professional and Pedagogical Practices of Postgraduate in Education Program of the West Paulista University, emerged from the following problematizing questions: What are the relations among the expectations of students and the proposals of identity formation, included in the Pedagogical Project of the Course (PPC) in the Higher Education Course of Technology (HECT) in Gastronomy, in a Federal Institute of the countryside of São Paulo State? What are the expectations of the entrepreneurs regarding to the entrants’ profile in this course? Does the PPC of this course consider the entrants’ expectations and the market demands? How well do the professors know the PCC and what are their expectations regarding to the future of their students? What is the qualitative profile of the course researched resulted from the semiotics analysis of the discourses emitted in the interviews carried out by the researcher with professors/students of the course and with the entrepreneurs? Based on these questions, it was defined the General Objective: Identifying and analyzing the qualitative profile of the identity formation of the HECT students in Gastronomy. The research had a qualitative approach, with document analysis and used semi-structured interviews with food sector entrepreneurs as well as students/professors of the course. The data analysis obtained from the discourse of the interviewees and from the document (PPC) was based in the Bakhtin’s semiotics (Discourse Analysis) and on the Theory of Content Analysis. This study generated the building of a Central Theme Axis named The establishment and Cultural Construction of Human and Professional Identity of the Academicians in Gastronomy, from which emerged seven (7) thematic frameworks that served as content basis to final interpretative analysis. The analysis explored the relation between the interviewees’ expectations and the formation proposals included in the PPC, in the identity formation process of students in this course. The research revealed that the PPC, even proposing a technicist formation, typical in Technology courses, announces the formation of a human and professional identity; however, the confront speeches of entrepreneurs, professors and students confirmed ideological differences in the conception of professional identity of these academicians. Thus, in its results, the study contributed to the specification of the qualitative profile of the entrant in the HECT in Gastronomy (in the researched Institution), based on the expectations of the entrants and on the expectations/necessities of the job market, it still pointed possible adjustments in the PPC, as well as in the professor’s performance to the fulfilment of the social functions of their given subjects.